The use of cattle grazing as a management tool for sustainable Mediterranean woodlands - Schoenbaum I.; Kigel J.; Yehuda Y.; Henkin Z. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Grazing has become an effective and accepted tool for managing open areas for different uses other than meat production, such as minimizing fire risk and increasing species diversity. Although woodlands in Israel are utilized for cattle grazing, the effect of grazing on woody vegetation has not been assessed quantitatively. The aim of this study was to characterize the effect of biotic and management factors, especially animal density, on the structure, composition and regeneration of woody vegetation. The study was conducted in the Western Galilee of Israel. A woodland plot of 211 ha was divided into four subplots, with two replications of two grazing intensities. Changes in the woody vegetation were monitored in 56 transects of 20 m length each, sampled at the onset of the study and after four annual grazing cycles. Woody plants up to height 2.1 meter growing along each transect were documented. From these records we derived indices to characterizing vegetation structure, woody biomass removal, species richness and woodland regeneration. It is shown that the extent of grazing effect depends mainly on cattle density, as well as on the type and state of the vegetation. The woody vegetation cover was reduced under the two grazing intensities, but grazing did not affect species richness and sapling abundance. Therefore, it was concluded that the use of cattle is an important tool for sustainable management of Mediterranean woodlands.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)